Dependence of Catalytic Activity of Prussian Blue Particles Towards Reduction of Hydrogen Peroxide on Their Size - DING, HAIYUN; ZHAO, LIPING; LI, YIJUN; HE, XIWEN (Asian Journal of Chemistry, 2010)
A study on the catalytic reduction of Prussian blue modified electrode to hydrogen peroxide was carried out in this paper. Prussian blue was modified on glassy carbon electrode (GCE) via cyclic voltammetric process in solution of 5 × 10-4 mol L-1 FeCl3 and 5 × 10-4 mol L-1 K3Fe(CN)6. The results indicated that the reduction of H2O2 on the Prussian blue modified electrode was controlled by diffusion. Moreover, Prussian blue modified electrodes with different sizes of Prussian blue particles exhibited different electrocatalytic activity to reduction of hydrogen peroxide. Lower amount and smaller size of Prussian blue particles modified on GCE gave a lower reduction signal and Prussian blue with smaller size exhibited improved catalytic activity to reduction of H2O2. Analytical performances of resulting Prussian blue based electrode have been studied in course of hydrogen peroxide detection by amperometry. Linear calibration range of sensor for H2O2 is over 1.3 × 10-7-2.1 × 10-4 mol L-1 with correlation coefficient of 0.999 and sensitivity of 887 mA M-1 cm-2. Average recovery of H2O2 in river water and whey was 101 and 103 %, respectively.